Determinant factors of sustainability for Bank Rakyat personal financing among government servants / K H Razali Zaman - Zaman, K H Razali (2011)
Customers are faced with an increasing choice of products and services and are becoming more demanding as they see banks competing to offer a higher level of service. Hence, it is very important for every financial institution and bank, to be geared up for a more competitive and challenging environment. This study is specially conducted to focus on Bank Kerjasama Malaysia Berhad (BKRM) Personal Financing since this is the most popular product of BKRM. It is felt that, intense competition it faces from other Islamic financial institution as well as the conventional ones makes it necessary to revise its infrastructure and marketing strategies so as to provide itself a leading edge over its competitors and expand its customer base with the opening of new opportunities and the expanding population. A total of 200 respondents who are also the customers of BKRM personal financing served as a sample of the study. This study assessed the key factors influencing this major contributor to the profit of the bank. Findings reveal that consumer choosing habit; features of product, marketing activities, facilities and services offered by BKRM seem to be the most important factors that contribute to sustainability of Bank Kerjasama Rakyat Malaysia.